128k views
1 vote
Need answer step by step

Need answer step by step-example-1

2 Answers

3 votes
17- we
=+\
Mdjsiw
Wow I’m
18394
User Becks
by
5.5k points
5 votes

Answer:

(-6, 2)

Explanation:

Multiply the second equation by 2

2x - 6y = -24

then add both equations together.

4x + 6y = -12

6x = -36, divide both sides by 6

x = -6

then plug -6 back into either equation and solve for y

-6 - 3y = -12

-3y = -6

y = 2

User Neil Dobson
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.